The Quality of Reporting of Intervention Studies in the Korean Journal of Women Health Nursing (KJWHN): Based on the TREND Guidelines - Myounghee Kim; Suk Hee Cheon; Eun Mi Jun; Sue Kim; Ju Eun Song; Sukhee Ahn; Hyun Ei Oh; Eun Joo Lee (Korean Society of Women Health Nursing, 2013)
PURPOSE: This study was done to evaluate quality of reports of non-randomized controlled quasi-experimental study articles published in the Korean Journal of Women Health Nursing (KJWHN). METHODS: A search was done for experimental studies assessing intervention effects among all articles published in the KJWHNfrom 2008 to 2013. Original articles were reviewed and analyzed according to the 22 checklist items of the guidelines for Transparent Reporting for Evaluations with Non-randomized Designs (TREND). RESULTS: Thirty-five articles on experimental studies were identified. The evaluation of the quality of reporting in these experimental studies found that there was a wide variety in the level of satisfying the TREND checklist. In particular, according to TREND topics, low levels of reporting quality were found for "title & abstract (only for information on how units were allocated to the intervention)", "outcomes in methods", "assignment in methods", "blinding in methods", "recruitment in results", "baseline data in results", "interpretation in discussion (especially intervention mechanism and success or barriers), "generalizability in discussion". CONCLUSION: Results indicate that adherence to TREND guidelines varied in experimental studies published in the KJWHN suggesting the recommendation that for higher levels of complete reporting, TREND guidelines be used in reports on experimental studies.